Imagen corporativa en la compañía de transporte pesado rutas Tixaneñas S.A. y el posicionamiento en el mercado de la Ciudad de Riobamba período 2017 - González Vilema, Joselyn Melisa (2019)
The present research work entitled: "Corporate Image in the Heavy Transport Company Rutas Tixaneñas S.A. and the positioning in the market of the City of Riobamba in the period 2017 ". It has objective, to determine that the corporate image of the company influences the market positioning, channeled to the customer's perception, defining strategies to be attractive to the public so that the company causes interest among customers. Also, clients achieve recorded in their minds the corporate image to get position the brand and facilitate sales about the service, which has had an impact on more significant economic benefit. The development of this research work consists of the following chapters that are: In chapter 1, the referential frame is established, where the problem, the justification and the objectives are posed. In chapter 2, the state of the art is detailed, and the theoretical framework where the dependent variable is conceptualized is the corporate image and the independent variable that is the market positioning. In chapter 3, corresponds to the methodological framework where the research method, type of research, research design, population, sample and techniques and data collection instruments are defined. Besides, it consists of the processing and discussion of results obtained in the surveys. Finally, in chapter 4, the conclusions and recommendations of the research are presented, based on the results achieved in the questionnaires.